2021
DOI: 10.1111/age.13158
|View full text |Cite
|
Sign up to set email alerts
|

Deletion in KRT75L4 linked to frizzle feather in Xiushui Yellow Chickens

Abstract: Bird feathers are the product of interactions between natural and artificial selection. Feather-related traits are important for chicken selection and breeding. Frizzle feather is characterized by the abnormally development of feathers in chickens. In the current study, frizzle feather characteristics were observed in a local breed called Xiushui Yellow Chicken in Jiangxi, China. To determine the molecular mechanisms that underlie frizzle feather in Xiushui Yellow Chicken, four populations of three breeds (Xiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Chickens (Chen, Xi, et al, 2022). The same trait is observed in crosses between a heterozygous frizzle rooster and wild-type hens, generated by a 69-bp deletion with autosomal incomplete dominant inheritance in the same gene (Ng et al, 2012).…”
Section: Cross-breed Comparisons and Independent Origins Of The Same ...mentioning
confidence: 70%
See 2 more Smart Citations
“…Chickens (Chen, Xi, et al, 2022). The same trait is observed in crosses between a heterozygous frizzle rooster and wild-type hens, generated by a 69-bp deletion with autosomal incomplete dominant inheritance in the same gene (Ng et al, 2012).…”
Section: Cross-breed Comparisons and Independent Origins Of The Same ...mentioning
confidence: 70%
“…Bruders et al, 2020;Domyan et al, 2014;Han et al, 2011;Krishnan & Cryberg, 2019;Krishnan, 2019;Maclary et al, 2023; , 2022). There are many studies, mostly in chickens, that show associations between SVs and feathering phenotypes (Chen, Xi, et al, 2022;Derks et al, 2018;Domyan et al, 2016;Dong et al, 2018;Elferink et al, 2008;Li et al, 2020;Li, Lee, et al, 2021;Mou et al, 2011;Ng et al, 2012;Shen et al, 2023); comb, muff and beard traits (Dorshorst et al, 2015;Guo et al, 2016;Imsland et al, 2012;Moro et al, 2015;Sato et al, 2010;Wang et al, 2017;Wright et al, 2009;Yang et al, 2020Yang et al, , 2021; and egg production (Cui et al, 2006;Huang et al, 2018;Lan et al, 2021;Manoharan et al, 2021;Vinh et al, 2021). Although less common, there are also associations between SVs and behaviour and domestication (Abe et al, 2013;Chen, Bai, et al, 2022;Falker-Gieske et al, 2023;Khatri et al, 2019;Komiyama et al, 2014;Krause et al, 2019;Rubin et al, 2010;Seol et al, 2019;Zhou et al, 2018;…”
Section: Identif Ying a Ssociations B E T Ween S Vs And Phenot Ypi C ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Whole genome resequencing in four populations of three chicken breeds identified a missense mutation (g.5281494A>G) and a 15-bp deletion (g.5285437-5285451delGATGCCGGCAGGACG) in KRT75L4 as candidate gene and mutations in Xiushui yellow chickens through comparative genomics and GWAS analysis to determine the molecular mechanism of frizzle feathers [ 21 ]. Moreover, two candidate mutations were confirmed in a large Xiushui yellow chicken population, and a 15-bp deletion in KRT75L4 was identified as the putative causative mutation of the frizzle feather [ 21 ]. Three independent selection signal analyses of Qilin chickens showed that the GGA33:1.17M-1.39M region was a significant selection region shared by the three detection methods based on whole genome resequencing data [ 46 ].…”
Section: Application Of Whole Genome Resequencing In Chickensmentioning
confidence: 99%
“…Indeed, many studies have been done to reveal artificial selection signatures on commercial broilers and layers (Rubin, et al 2010; Elferink, et al 2012; Qanbari, et al 2012; Fan, et al 2013; Gheyas, et al 2015; Boschiero, et al 2018; Qanbari, et al 2019) as well as on indigenous chickens (Guo, et al 2016; Wang, et al 2016; Wang, et al 2017; Zhang, Yang, et al 2017; Bortoluzzi, et al 2018; Lawal, et al 2018; Wang, Li, et al 2020). These studies have identified genes or quantitative trait loci (QTLs) related to specific traits such as body size (Kerje, et al 2003; McElroy, et al 2006; Wang, et al 2016; Wang, et al 2017; Wang, Bu, et al 2020; Wang, Cao, et al 2020; Zhang, et al 2020; Wang, Hu, et al 2021), meat quality (Jennen, et al 2005; Bihan-Duval, et al 2018; Moreira, et al 2018), egg production (Zhao, et al 2021), feathering (Zhao, et al 2016; Guo, et al 2018; Zhang, et al 2018; Yang, et al 2019; Bortoluzzi, et al 2020; Li, Lee, et al 2020; Chen, et al 2022; Qiu, et al 2022), plumage color (Zhang, Liao, et al 2017; Huang, Pu, et al 2020; Huang, Otecko, et al 2020; Nie, et al 2021), skin color (Li, Sun, et al 2020), behaviors (Luo, et al 2020; Mehlhorn and Caspers 2020), immunity (Zou, et al 2020), crest shapes (Li, Lee, et al 2021), bone traits (Wang, et al 2018; Li, Liu, et al 2021; Kondoh, et al 2022), rumpless trait (Noorai, et al 2012; Freese, et al 2014; Xu, et al 2017; Wang, Khederzadeh, et al 2021), and polydactyly (Zhang, et al 2016; Chu, et al 2017). However, genetic bases of many artificially selected traits, in particular, of indigenous chickens, are far from being fully understood.…”
Section: Introductionmentioning
confidence: 99%